Fighting customer churn rate: an exploration of customer defection in financial services - Ferreira, Fernando Lamounier (2019)
Several papers have related customer churn with customer relationship management (CRM) in a wide range of industries. Few empirical studies have analyzed the Brazilian Consortium segment deeply in order to evaluate customer churn regarding financial literacy level, which is defined by “the ability to make informed judgments and to take effective decisions regarding the use of management of money” (ANZ Banking Group, 2015, p. 02). Thereby, this paper first examines the relationship between customer financial literacy and customer churn to then investigate the reasons why customers churn in a Brazilian Consortium company. To explain this question holistically, a mixed-method was chosen. In the quantitative part, a survey was conducted to measure the financial literacy of 2,004 customers of that Consortium company. These consumers were tracked for three months after signing the contract and were then segmented in two different groups: churners and non-churners. Eventually, the author could compare the financial literacy level between both groups to verify any meaningful difference. In the qualitative part, a semi-structured interview was carried out with 12 churners to identify the reasons why they have defected. The results prove that churners have a lower financial literacy level, but it has no practical relevance since there is a minimum difference between both means. Ultimately, the findings suggest three main reasons for customer defection: 1) Misleading Negotiation, 2) Financial Restraints, and 3) Customer Withdraw. In the end, managerial implications are discussed and proposed.